Ժողովրդամշակութային արտացոլումները առակագրության ժանրում - Սիրարփի Գույումջյան (ՀՀ ԳԱԱ հրատ.)
This paper is about the reflection of ethnic-cultural characteristic features in fables. Language as a symbol of the culture of that nation characterizes the national approaches to different economic, political, social and other aspects of life.
Keywords: Ethnography; Folk literature; Language and Literature